Utilizing depleted oil reservoirs for in-situ biohydrogen production: addressing knowledge gaps, sustainable pathways and future research directions - Abutu, David; Wan Mohd Hafizuddin, Wan Yussof; Nwaichi, Peter Ikechukwu; Umunnawuike, Chika; Nyah, Francis; Money, Barima; Agi, Augustine Aja (Elsevier, 2026)
Depleted hydrocarbon reservoirs, which were once a primary source of fossil fuels, now pose significant environmental and economic challenges, including methane leakage, land subsidence, and high decommissioning costs. Repurposing these reservoirs for in-situ biohydrogen production presents a new approach to sustainable energy generation while mitigating environmental hazards. This review explores the potential of depleted reservoirs as biohydrogen reactors, leveraging microbial consortia to ferment residual hydrocarbons and produce hydrogen under controlled subsurface conditions. However, several knowledge gaps remain, particularly in understanding microbial adaptability, optimizing reservoir geochemistry, and developing efficient nutrient injection strategies. The review also examines sustainable pathways, such as integrating biohydrogen production with carbon sequestration to enhance energy recovery while reducing greenhouse gas emissions. Furthermore, future research directions, including reservoir simulation modeling, synthetic microbial engineering, and pilot-scale field demonstrations were identified, to improve process viability. By addressing these challenges, depleted oil reservoirs could serve as cost-effective, large-scale biohydrogen production sites, supporting the global transition to clean energy while repurposing existing infrastructure for sustainable applications.